Analysis of Elementary School Students’ Mathematical Literacy Abilities Through Diagnostic Assessments Based on Metacognitive Abilities at Field Experience Practice In-Service Teacher Professional Program - Tarusu, Deysti T.; Makawawa, Junita C. (International Journal of Information Technology and Education, 2024)
The importance of the relationship between mathematical literacy skills and higher-order thinking skills is in line with the 3 competencies needed in the 21st century. Mathematical literacy skills are very important for students to understand the function of mathematics in everyday life through the formulation, use, and interpretation of mathematics in various contexts. This research aims to analyze and describe the mathematical literacy abilities of elementary school students through diagnostic assessments based on metacognitive abilities at PPL PPG Daljab. The type of research used in this research is descriptive qualitative with research subjects of 60 elementary school students who were reviewed through a diagnostic assessment based on metacognitive abilities. data collection through test results and questionnaire results. Data reduction, data presentation, and conclusion drawing are carried out in data analysis. The research results obtained are that applying innovative learning models or methods can improve and develop the mathematical literacy skills of elementary school students, especially class V. So, teachers need to familiarize students with working on story problems, especially open-ended type story problems, and innovate in learning to motivate them. students to be actively and directly involved in the problem-solving process so that they can improve students mathematical literacy skills.